Nilai-Nilai Filosofis dalam Tradisi Budaya “Tunggu Tubang” pada Suku Semende - Oktariyani; Ratna Said; Ninin Herlina; Eva Nurchurifiani (Medan Resource Center, 2026)
This study examines the philosophical values embedded in the Tunggu Tubang tradition of the Semende Tribe, a customary inheritance system that assigns responsibility to the eldest daughter in sustaining family continuity and preserving ancestral heritage. The research addresses how these values shape social identity and contribute to character formation within the community. Employing a qualitative descriptive approach, data were collected through in-depth interviews, participant observation, and a comprehensive literature review. The findings reveal that the Tunggu Tubang tradition embodies interconnected values, including religious, leadership, cultural, and moral dimensions, which collectively guide individual conduct and social responsibility. These values function not only as normative principles for individuals entrusted with the Tunggu Tubang role but also as a broader ethical framework that reinforces communal cohesion and intergenerational continuity. The study argues that the philosophical foundation of this tradition holds significant relevance for contemporary character education, particularly in strengthening local wisdom and cultural resilience among younger generations.